2009
DOI: 10.1093/bioinformatics/btp205
|View full text |Cite
|
Sign up to set email alerts
|

Model-based clustering of array CGH data

Abstract: Motivation: Analysis of array comparative genomic hybridization (aCGH) data for recurrent DNA copy number alterations from a cohort of patients can yield distinct sets of molecular signatures or profiles. This can be due to the presence of heterogeneous cancer subtypes within a supposedly homogeneous population.Results: We propose a novel statistical method for automatically detecting such subtypes or clusters. Our approach is model based: each cluster is defined in terms of a sparse profile, which contains th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
(52 reference statements)
0
14
0
Order By: Relevance
“…WECCA was also found to define a common T-MF and SS group, a T-MF-only group, and a group composed of most CALCL cases, although some cases were not found in the relevant clinical category. Indeed, different algorithms were found to provide nearly identical results for clustering (Blaveri et al, 2005;Shah et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WECCA was also found to define a common T-MF and SS group, a T-MF-only group, and a group composed of most CALCL cases, although some cases were not found in the relevant clinical category. Indeed, different algorithms were found to provide nearly identical results for clustering (Blaveri et al, 2005;Shah et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, clustering by giving weight to specific chromosomal regions, as with WECCA or other algorithms, would help to individualize prognostic groups by compiling data from different platforms. Such algorithms have been mainly applied to BAC array data with a uniform distribution of probes across the genome (Van Wieringen et al, 2008;Shah et al, 2009;Takeuchi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Significant clusters were identified using a confidence level of 0.05. A second method was applied by running the hmmMix software [33] to identify three clusters with default parameters. Integer copy numbers were converted to log2(copy number/ploidy) values for each cytoband as input for hmmMix.…”
Section: Unsupervised Clustering Of Samplesmentioning
confidence: 99%
“…Similar results were obtained when the analysis was restricted to include only the subset of stage III and IV samples from the TCGA cohort (see Supplementary material, Figure S2), or using Euclidean rather than correlation-based distances (see Supplementary material, Figure S3). We repeated the analysis using a model-based clustering method (hmmMix [33]; see Materials and methods) to assess whether an independent, non-hierarchical approach method would produce comparable results. Analyses in which the algorithm was instructed to group samples into three to 10 clusters consistently revealed that spatially separated biopsies from the same tumour resided in different DNA copy number clusters.…”
Section: Intratumour Heterogeneity In Copy Number Profilesmentioning
confidence: 99%
“…Existing methods for aCGH analysis include algorithms for smoothing, segmentation and combined segmentation and classification of both single- [8], [9], [10], [11], [12], [13] and multi-sample data [14], [15], [16], [17], [18], [19], [20]. Such methods can be highly effective at identifying discrete copy number variations in such data, but are poorly suited to the problem of phylogenetic inference because they do not constrain solutions to common markers across tumor samples.…”
Section: Introductionmentioning
confidence: 99%